Plasmodium falciparum: programmed cell death in the erythrocytic stages - Engelbrecht, Dewaldt (My University, 2015)
Plasmodium falciparum is responsible for the majority of global malaria deaths. During the pathogenic blood stages of infection, a rapid increase in parasitaemia threatens the survival of the host before transmission of slow-maturing sexual parasites to the mosquito vector to continue the life cycle. Programmed cell death (PCD) may provide the parasite with the means to control its burden on the host and thereby ensure its own survival. PCD in P. falciparum remains a poorly understood and controversial topic. A gathering body of evidence suggests P. falciparum is capable of PCD, but there are conflicting results regarding the phenotype. This study represents a comprehensive phenotypical characterisation of cell death in intraerythrocytic P. falciparum after various physiologically relevant stress stimuli, including high parasitaemia, heat stress simulating febrile paroxysms, and exposure to natural sunlight. The latter is a novel stimulus for PCD studies in P. falciparum. Biochemical markers of cell death, including DNA fragmentation, mitochondrial dysregulation and phosphatidylserine externalisation on parasitized erythrocytes, were used to provide a holistic description of cell death. Data showed that the combination of cell death markers varied with different stress stimuli and with the developmental stage of the parasite. An apoptosis-like phenotype, characterised by mitochondrial depolarisation, DNA fragmentation and phosphatidylserine externalisation, was suggested after stress from high parasitaemia. Heat stress affected ring stage parasites more severely than previous data suggested and induced an apoptosis-like phenotype. In contrast, late stage parasites showed markers of an autophagic-like cell death, including slight DNA fragmentation, phosphatidylserine externalisation and cytoplasmic vacuolisation. Sunlight exposure induced markers of PCD that included DNA fragmentation preceding mitochondrial hyperpolarisation, but the phenotype was not clear. The paradigm of PCD in P. falciparum is a dynamic and ever-evolving one that will continue to challenge our thinking and understanding of how the world’s deadliest parasitic killer can induce its own death to limit damage on the host. Evidence indicates that P. falciparum undergoes PCD and that the phenotype(s) may be unique. PCD is an important feature of P. falciparum biology and the elucidation of parasite PCD pathway(s) that differ from host mechanisms may yield novel drug targets.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. This thesis is presented as a series of publications and unpublished data. Johannesburg, 2015